Traders' Dilemma Developing Countries' Response To Trade Disputes - Devarajan, Shantayanan (World Bank E-Library Archive, 2018)
If trade tensions between the United States and certain trading partners escalate into a full-blown trade war, what should developing countries do? Using a global, general-equilibrium model, this paper first simulates the effects of an increase in U.S. tariffs on imports from all regions to about 30 percent (the average non-Most Favored Nation tariff currently applied to imports from Cuba and the Democratic Republic of Korea) and retaliation in kind by major trading partners-the European Union, China, Mexico, Canada, and Japan. The paper then considers four possible responses by developing countries to this trade war: (i) join the trade war; (ii) do nothing; (iii) pursue regional trade agreements (RTAs) with all regions outside the United States; and (iv) option (iii) and unilaterally liberalize tariffs on imports from the United States. The results show that joining the trade war is the worst option for developing countries (twice as bad as doing nothing), while forming RTAs with non-U.S. regions and liberalizing tariffs on U.S. imports ("turning the other cheek") is the best. The reason is that a trade war between the United States and its major trading partners creates opportunities for developing countries to increase their exports to these markets. Liberalizing tariffs increases developing countries' competitiveness, enabling them to capitalize on these opportunities